Konceptualizowanie uczuć jako specyfika opisu przeżyć w tekstach uczniowskich - Szczerbińska, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The aim of the article is to analyze the development of the description of experiences and the conceptualisation of feelings in the school essays. The author analyzes the proper part of the description of experiences prepared by primary school students; the interpretation consists of both treating the text as a product – the effect of using technology in the process of linguistic activity – as well as introducing the students’ textual abilities and skills. The analyzed texts include the authors’ own interpretations of their experiences, starting from the presentation of stimuli that triggered the given feelings, through describing the accompanying and emotional reactions, and ending with the description of the results derived from the experienced emotions. The essence of the description of experiences is the conceptualization of feelings, for the development of which students use three different schemas: simple time sequences, the contrast technique and the “kaleidoscope technique”.
Keywords: description of experiences; feelings; description technique; composition; stylistic traces